The effects of regular cold-water immersion use on training-induced changes in strength and endurance performance: a systematic review with meta-analysis - Malta, E. S.; Dutra, Y. M.; Broatch, J. R.; Bishop, D. J.; Zagatto, A. M. (Sports Medicine, 2021)
Background: Cold-water immersion (CWI) is one of the main recovery methods used in sports, and is commonly utilized as a means to expedite the recovery of performance during periods of exercise training. In recent decades, there have been indications that regular CWI use is potentially harmful to resistance training adaptations, and, conversely, potentially beneficial to endurance training adaptations. The current meta-analysis was conducted to assess the effects of the regular CWI use during exercise training on resistance (i.e., strength) and endurance (i.e., aerobic exercise) performance alterations. Methods: A computerized literature search was conducted, ending on November 25, 2019. The databases searched were MEDLINE, Cochrane Central Register of Controlled Trials, and SPORTDiscus. The selected studies investigated the effects of chronic CWI interventions associated with resistance and endurance training sessions on exercise performance improvements. The criteria for inclusion of studies were: (1) being a controlled investigation; (2) conducted with humans; (3) CWI performed at = 15 °C; (4) being associated with a regular training program; and (5) having performed baseline and post-training assessments. Results: Eight articles were included before the review process. A harmful effect of CWI associated with resistance training was verified for one-repetition maximum, maximum isometric strength, and strength endurance performance (overall standardized mean difference [SMD] = - 0.60; Confidence interval of 95% [CI95%] = - 0.87, - 0.33; p < 0.0001), as well as for Ballistic efforts performance (overall SMD = - 0.61; CI95% = - 1.11, - 0.11; p = 0.02). On the other hand, selected studies verified no effect of CWI associated with endurance training on time-trial (mean power), maximal aerobic power in graded exercise test performance (overall SMD = - 0.07; CI95% = - 0.54, 0.53; p = 0.71), or time-trial performance (duration) (overall SMD = 0.00; CI95% = - 0.58, 0.58; p = 1.00). Conclusions: The regular use of CWI associated with exercise programs has a deleterious effect on resistance training adaptations but does not appear to affect aerobic exercise performance.